White hot hate: a true story of domestic terrorism in America's heartland - Lehr, Dick (Mariner Books, 2021)
"For fans of I'll Be Gone in the Dark, the thrilling true story of a would-be terrorist attack against a Kansas farming town's immigrant community, and the FBI informant who exposed it. In the spring of 2016, as immigration debates rocked the United States, three men in a militia group known as the Crusaders grew aggravated over one Kansas town's growing Somali community. They decided that complaining about their new neighbors and threatening them directly wasn't enough. The men plotted to bomb a mosque, aiming to kill hundreds and inspire other attacks against Muslims in America. But they would wait until after the presidential election, so that their actions wouldn't hurt Donald Trump's chances of winning. An FBI informant befriended the three men, acting as law enforcement's eyes and ears for six months. His secretly taped conversations with the militia were pivotal in obstructing their plans and were a lynchpin in the resulting trial and convictions for conspiracy to use a weapon of mass destruction. White Hot Hate will tell the riveting true story of an averted case of domestic terrorism in one of the most remote towns in the US, not far from the infamous town where Capote's In Cold Blood was set. In the gripping details of this foiled scheme, we see in intimate focus the chilling, immediate threat of domestic terrorism-and racist anxiety in America writ large. "--